Novel metal–organic framework materials: blends, liquids, glasses and crystal–glass composites. Issue 60 (2nd May 2019) - Tuffnell, Joshua M.; Ashling, Christopher W.; Hou, Jingwei; Li, Shichun; Longley, Louis; Ríos Gómez, María Laura; Bennett, Thomas D.
Abstract : This Feature Article reviews a range of amorphisation mechanisms of Metal–Organic Frameworks (MOFs) and presents recent advances to produce novel MOF materials including porous MOF glasses, MOF crystal–glass composites, flux melted MOF glasses and blended zeolitic imidazolate framework glasses. Abstract : Metal–organic frameworks (MOFs) are often, and incorrectly, believed to be purely crystalline solids. This Feature Article highlights a selection of highly disordered MOF-based materials. This disorder gives rise to numerous possibilities in the fabrication of new MOF materials, and presents an alternative method of novel materials discovery, outside of the synthesis of increasingly complex crystalline structures. The formation of liquid MOFs and resultant melt-quenched glasses is reviewed, along with several categories of novel MOF-based materials including blends, flux melted glasses and crystal–glass composites.